Competitive Inoculation as an Effective Prophylaxis Against Recurrent Urinary Tract Infections: A Systematic Review - Quentin Mak; Julian Greig; Kamran Ahmed; Shamim Khan; Prokar Dasgupta; Sachin Malde; Nicholas Raison (International Neurourology Journal, 2023)
Urinary tract infection (UTI) is a common condition defined as the presence of bacteria within the urine above a certain threshold (usually >100,000 m/L). The lifetime risk in women is estimated to be 50%, of whom 25% will develop recurrence within 6 months. Unfortunately, the use of antibiotics to treat and manage recurrent UTI (rUTI) is a growing problem, due to the burden of growing antibiotic resistance on public health. As such, new approaches to manage rUTI are being investigated and developed. Competitive inoculation via instillation of Escherichia coli 83972 or HU2117 in the bladder is a new prophylactic non-antimicrobial therapy for rUTIs. It utilizes the principle of the protective nature of asymptomatic bacteriuria to prevent recurrence of symptomatic UTIs. However, the effectiveness and safety of this technique remains unclear. This systematic review examined the current outcomes data on competitive inoculation as an effective and safe treatment for rUTI prophylaxis. Based on a limited number of studies, current evidence suggests that competitive inoculation is an effective and safe prophylactic measure against UTIs in a select group of patients with incomplete bladder emptying. However, administration of the technology is both resource and time intensive, and there is strong data demonstrating low successful colonisation rates. Competitive inoculation is an alternative to antibiotics only to rUTI patients with incomplete bladder emptying. There is no evidence to suggest that the technology would be suitable for other subsets of rUTI patients. Further randomized controlled trials should be conducted to improve the evidence base before drawing conclusions for clinical practice, and ideas to improve colonisation rates and simplify the administration process should be explored.